A brief review of the current knowledge on environmental toxicants and risk of pediatric cancers. (3rd April 2022) - Shakeel, Omar; Lupo, Philip J.; Strong, Simon; Arora, Manish; Scheurer, Michael E.
Abstract: The incidence of pediatric cancers has steadily increased since 1975, which could suggest that other exogenous factors are accounting for an increasing proportion of cases. There has been growing concern over environmental exposures (i.e., toxicants) the on development of pediatric cancers. However, identifying environmental exposures on childhood cancer risk has been challenging because these outcomes are infrequent compared to cancer in adults, and it is difficult to estimate exposure during specific critical periods of development (e.g., pre-conception, in utero, early childhood) that are likely more important for childhood cancer development. Here, we summarize the International Agency for Research on Cancer (IARC) Group 1 agents (toxicants known to be carcinogenic to humans), their routes of exposure, current methods for risk mitigation, and what is known of their associations with pediatric cancer risk. Our review suggests that environmental toxicants are important and potentially modifiable risk factors that need to be more fully explored in children and adolescents.